Climate change, agriculture, food and nutrition security policies and frameworks in Kenya - Radeny, Maren A.O.; Mungai, Catherine; Amwata, Dorothy; Osumba, Joab J.L.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This paper reviews the current state of policies and frameworks on climate change, agriculture, food, and nutrition security in Kenya. Integrating climate change in policies and frameworks on agriculture, food and nutrition security is important for providing and strengthening the enabling environment for building farmers resilience and adaptive capacity. Similarly, climate change policies and frameworks need to integrate agriculture, food and nutrition security. In addition, the paper reviews some of the regional, continental, and global frameworks on climate change, agriculture and food security of relevance to Kenya. The paper combines a review of relevant literature, policies and frameworks on climate change, agriculture, food and nutrition security with expert interviews. The review shows that most climate change policies and frameworks integrate agriculture, food and nutrition security, with the majority prioritizing agricultural productivity and food availability. Similarly, most of the agriculture, food and nutrition security policies and frameworks integrate climate change adaptation, with very limited focus on mitigation. Mitigation is often considered as an adaptation co-benefit, thus adaptation actions that have mitigation benefits are highly prioritized. In particular, the recent policies and frameworks are aligned with the regional, continental and global frameworks such as the Sustainable Development Goals (SDGs), the Comprehensive African Agriculture Development Programme (CAADP), and the Paris Agreement. The review also shows that a number of institutions in Kenya are working on climate change and agriculture, with institutional overlaps in some cases in focus areas of interventions. Strengthening institutional arrangements and coordination may help consolidate and promote partnerships among independent institutional efforts.